Beyond the project: Building a strategic theory of change to address dementia care, treatment and support gaps across seven middle-income countries. (January 2022) - Breuer, Erica; Comas-Herrera, Adelina; Freeman, Emily; Albanese, Emiliano; Alladi, Suvarna; Amour, Rochelle; Evans-Lacko, Sara; Ferri, Cleusa P; Govia, Ishtar; Iveth Astudillo García, Claudia; Knapp, Martin; Lefevre, Michael; et al.
Evidence from middle-income countries indicates high and increasing prevalence of dementia and need for services. However, there has been little investment in care, treatment or support for people living with dementia and their carers. The Strengthening Responses to Dementia in Developing Countries (STRiDE) project aims to build both research capacity and evidence on dementia care and services in Brazil, Indonesia, India, Jamaica, Kenya, Mexico and South Africa. This article presents the Theory of Change (ToC) approach we used to co-design our research project and to develop a strategic direction for dementia care, treatment and support, with stakeholders. ToC makes explicit the process underlying how a programme will achieve its impact. We developed ToCs in each country and across the STRiDE project with researchers, practitioners, people living with dementia, carers and policymakers at different levels of government. This involved (1) an initial ToC workshop with all project partners (43 participants); (2) ToC workshops in each STRiDE country (22–49 participants in each); (3) comparison between country-specific and overall project ToCs; (4) review of ToCs in light of WHO dementia guidelines and action plan and (5) a final review. Our experiences suggest ToC is an effective way to generate a shared vision for dementia care, treatment and support among diverse stakeholders. However, the project contribution should be clearly delineated and use additional strategies to ensure appropriate participation from people living with dementia and their carers in the ToC process.